KEMAMPUAN KINERJA GURU MTS HIFZIL QUR’AN YAYASAN ISLAMI CENTER SUMATERA UTARA DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) - Salsabila Yasmin; Abdul Fattah Nasution; Arya Tantri; Rahmad Riadi Batubara (Cendekia Madani Nusantara, 2024)
This research looks at the difficulties and solutions faced by teaching staff in developing interesting and relevant lesson plans for students at MTs Hifzil Qur'an Yayasan Islami Center North Sumatra. In addition, it also analyzes the ability of teacher performance in the process of making Lesson Plans (RPP). Through interviews with teachers and principals, it is known that the creation of lesson plans must be based on the syllabus, which serves as the main framework for identifying basic abilities. Teachers face many obstacles, including time constraints, poor resources and requirements for adaptability. Nonetheless, educators show originality and creativity by modifying lesson plans according to students' needs and the classroom environment, and by applying techniques such as ice-breaking games to increase students' interest. Madrasah leaders play an important role in guiding and assisting educators and ensuring that classroom plans adhere to established criteria. The findings of this study suggest that to improve the quality of lesson planning and implementation and provide more engaging and effective teaching, adequate facility assistance and strong academic supervision are essential.